Improving Healthcare Experiences for Transgender and Intersex Populations - Destiny S.J. Lee; Joanne Chopak-Foss (Georgia Southern University, 2023)
Intersex is an umbrella term for individuals who are born with sex characteristics that do not typically fall into male or female categories. Individuals who are intersex make up about 1.7% of the United States population today and are identified within the lesbian, gay, bisexual, transgender, and intersex (LGBTQIA+) community. Many people who are intersex identify as transgender, which relates to the social process of gender change, as they develop into adults. In Georgia, approximately 4% of the population identify as LGBTQIA+. The purpose of this paper is to increase awareness of the perceived discrimination from healthcare providers, non-inclusive organizational practices, and lack of skilled providers that serve as barriers to healthy outcomes for transgender and intersex individuals. Culturally competent care is necessary for physicians to provide an openly safe environment for people who are LGBTQIA+ to help improve their comfort level to disclose their health information. Recommendations for physicians caring for people who are LGBTQIA+ to incorporate into their clinics include: having acceptable advertising practices, educating staff and providers, maintaining biases, and providing inclusive intake forms.